2019
DOI: 10.1080/13645579.2019.1593378
|View full text |Cite
|
Sign up to set email alerts
|

The use of body-mapping in interpretative phenomenological analyses: a methodological discussion

Abstract: The increasing popularity of Interpretative Phenomenological Analysis (IPA) in social research brings an increasing criticism about its validity, robustness and, more recently, its lack of expressive features. Recently, the novel arts-based research approach called body-mapping was recognized as enhancing social science research in creative and nuanced ways. Body-mapping allows for unique insights into participants' lived experiences, the meaning thereof, and into how meaning is impacted by their socio-cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We did not recruit birth trauma survivors. People who have participated in body mapping exercise have often reported a positive experience and have found the experience interesting, entertaining, empowering, helpful and a great opportunity to think reflectively and creatively (Coetzee et al, 2019; Klein & Milner, 2019; Lys, 2018; Orchard, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not recruit birth trauma survivors. People who have participated in body mapping exercise have often reported a positive experience and have found the experience interesting, entertaining, empowering, helpful and a great opportunity to think reflectively and creatively (Coetzee et al, 2019; Klein & Milner, 2019; Lys, 2018; Orchard, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that arts-based research methods, such as body mapping, tend to minimize power-based imbalances between researcher and participant. It reverses the traditional the power dynamics to present the participant as the expert knowledge producer and the researcher as the facilitator and co-creator of the outcome of the arts-based research (Boydell et al, 2018(Boydell et al, , 2020Klein & Milner, 2019;Lys, 2018;Sweet and Escalante 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Marisa) Sweet and Escalante (2015) describe that body experiences are based on cultural and social practices, which allow body feelings (sensations, moods, and states of being) to be a means of detecting and incorporating these experiences. By exploring the experiences directing them to the embodied representation, the BMST confers the possibility of reinforcing embodied knowledge and communicating the meanings that this knowledge acquires in the face of an individual repertoire (Klein & Milner, 2019).…”
Section: Overarching Theme and Thematic Categoriesmentioning
confidence: 99%
“…The BMST enabled the valuing of personal knowledge (Klein & Milner, 2019); engaged consciousness about experiential experiences by turning to experience with the body (Lys, 2018); and contemplated cognitive aspects, as it integrates somatic experience with mental processes (McCorquodale & De Luca, 2020). Thus, the representations expressed the body as a means of knowledge acquisition owing to its centrality in everyday experiences, as assumed by Collings & Smith (2020).…”
Section: Overarching Theme and Thematic Categoriesmentioning
confidence: 99%